Legal Guarantees for Persons with Disabilities to Secure Decent Work: A Human Rights Perspective from Indonesia - S., Laurensius Arliman; Ratnawati, Elfrida; Razak, Aida Abdul (Jurnal Wawasan Yuridika, 2024)
Employment rights for people with disabilities are often neglected due to the lack of respect for equality before the law and respect for human rights. This study aims to examine: (1) the position and role of national and international law in regulating the right to work for people with disabilities; and (2) the implementation of regulations regarding the right to work for people with disabilities in Indonesia from a human rights perspective. Using normative legal research. The results of the study indicate that the international legal framework, especially the Convention on the Rights of Persons with Disabilities (CRPD), which has been ratified through Law Number 19 of 2011, provides a strong foundation for the recognition and protection of employment rights for people with disabilities. At the national level, this regulation is strengthened by the 1945 Constitution, Law Number 13 of 2003 concerning Employment, and Law Number 8 of 2016 concerning Persons with Disabilities. The impact of this study is that it must strengthen the implementation of non-discrimination experienced by people with disabilities in the world of work.